Corporate meetings market in Singapore : hotels' perspectives. - Sng, Michelle Mei Kim. (2008)
This study seeks to provide a better understanding of the corporate meetings market in Singapore and the focus is on hotels, a key industry partner of the STB. Sales & Marketing Directors from ten hotels were interviewed and their opinions and suggestions are noted while interviewers' recommendations are also made.